Microbial biostimulants as alternatives for the rooting of olive tree cuttings (Bioscience Journal, 2022)
Currently, southern Minas Gerais (MG) state is an important producer of different olive tree (Olea europaea L.) cultivars because, in this region, the plants can differentiate the buds to produce flowers and fruit. To stimulate the rooting of cuttings, the synthetic hormone indole-3-butyric acid (IBA) at a concentration of 3 g L−1 is used commercially. However, few studies have investigated arbuscular mycorrhizal fungi (AMF), isolated or combined with rhizobacteria, as a biotechnological tool to produce hormones that function in the rooting of olive tree cuttings. The aim of this study was to evaluate the capacity of different AMF species (Rhizophagus clarus, Gigaspora rosea, or Acaulospora scrobiculata), combined or not with IBA or rhizobacteria, to promote the rooting of three olive tree cuttings (Arbequina, Grappolo 541, and Maria da Fé) with potential for cultivation in this region. For this, three experiments were conducted at the Experimental Farm of EPAMIG in Maria da Fé (MG), and the rooting potential of the olive tree cuttings inoculated with I) AMF, II) AMF combined with increasing doses of IBA, and III) AMF combined with three isolates of rhizobacteria was evaluated. The inoculation of olive tree cuttings of cultivars Arbequina, Grappolo 541, and Maria da Fé with Rhizophagus clarus, Gigaspora rosea, or Acaulospora scrobiculata combined or not with IBA or rhizobacteria did not significantly promote rooting. Alternative forms of rooting olive tree cuttings are still a challenge, and further studies for standardizing methodologies and experimental conditions are required.